Early prediction of physical inactivity in 215 individuals 6 months after a mild stroke: The fall study of Gothenburg - Carina U. Persson; Per-Olof Hansson (Medical Journals Sweden, 2020)
Objective: To determine the frequency of, and factors associated with, physical inactivity 6 months post-stroke. Design: Prospective longitudinal cohort. Patients: A total of 215 consecutively included individuals with mild acute stroke from the Fall Study of Gothenburg. Methods: Physical activity level was assessed using the 4-level Saltin-Grimby Physical Activity Scale. Associations between independent variables and the dependent variable physical inactivity 6 months post-stroke were identified using univariable and multivariable logistic regression analyses. Results: At 6 months post-stroke, 81 individuals (37.7%) reported physical inactivity. Physical inactivity at 6 months after a mild stroke were associated with: stroke severity, odds ratio (OR) 1.29 (95% confidence interval (95% CI) 1.01-1.66, p = 0.043); physical inactivity prior to stroke, OR 2.89 (95% CI 1.39-6.04, p = 0.0046); moderate postural control, OR 6.71 (95% CI 2.48-18.16, p = 0.0002); poor postural control, OR 2.55 (95% CI 1.19-5.48, p = 0.016); and number of drugs in acute stroke, OR 1.20 (95% CI 1.06-1.35, p = 0.0046). Conclusion: In this exploratory study, almost 40% of subjects reported physical inactivity 6 months after an acute mild stroke. Predictors of physical inactivity were physical inactivity before stroke and greater stroke severity, impaired postural control and a higher number of drugs in acute stroke.